Net Neutrality matters: Privacy antibodies for information monopolies and mass profiling | Neutralidade da rede importa: anticorpos de privacidade para monopólios de informação e profiling em massa - Riva, Gianluigi M.; Barry, Marguerite (Revista Publicum, 2019)
Abstract: Profiling activities used to personalise user content can place online corporations in a position of significant influence over user behaviour. The ability to deliver different search engine results, news feeds, discriminatory prices, and so forth, can be exploited to grant unequal access to different kinds of content. This is likely to intensify with the Internet of Things (IoT), which will surround individuals with sensors capable of 24/7 full tracking. This content-shaping power jeopardises the neutral accessibility that a democratic internet should ensure. Indeed, both neutrality and accessibility should refer not only to the service connection but also to the content it delivers. This study examines this personalisation and filtering power in light of Privacy and Data Protection regulations to explore how privacy principles can be used to enhance IoT accessibility. It elaborates a comparative analysis of legislative sources related to public goods and interests, data flows and contract law relationships, into a holistic narrative reasoning. The discussion addresses the monopolistic economic position of platforms, their connected revenue models and the power to control and influence information. Fake news plays a crucial role in this and is addressed consequently. Therefore, the study analyses how these factors together could form profiling ‘multi-monopolies’ in connection with a non-neutral Internet of Things. Furthermore, techniques of influence have more grip where there is a lack of awareness and knowledge, and a new model of digital “divide et impera” seems to enhance these phenomena. Besides, social score systems and discriminatory pricing can be powerful tools in this sense. We discuss the gap between regulatory approaches and real-world situations, offering common legal tools and Privacy by Design (PbD) as potential solutions for neutral accessibility. We highlight how the current regulatory framework requires more harmonisation to guarantee effective user protections, especially in an IoT ecosystem. Resumo: As atividades de profiling usadas para personalizar o conteúdo disponibilizado aos usuários podem colocar as empresas de Internet em uma posição de influência significativa sobre o seu comportamento. A capacidade de fornecer diferentes resultados de mecanismos de pesquisa, feeds de notícias, preços discriminatórios, dentre outras, pode ser explorada para garantir acesso desigual a diferentes tipos de conteúdo. É provável que isso se intensifique com a Internet das Coisas (IoT), que cercará indivíduos com sensores capazes de rastreamento completo 24 horas por dia, 7 dias por semana. Esse poder de modelagem de conteúdo põe em risco a acessibilidade neutra que uma Internet democrática deve garantir. De fato, tanto a neutralidade quanto a acessibilidade devem se referir não apenas à conexão do serviço, mas também ao conteúdo que ele fornece. Este estudo examina esse poder de personalização e filtragem à luz dos regulamentos de Privacidade e Proteção de Dados para explorar como os princípios de privacidade podem ser usados para aprimorar a acessibilidade da IoT. Elabora-se uma análise comparativa de fontes legislativas relacionadas a bens e interesses públicos, fluxos de dados e relações de direito contratual, em um raciocínio narrativo holístico. A discussão aborda a posição econômica monopolista das plataformas, seus modelos conectados de receita e o poder de controlar e influenciar as informações. Fake news desempenham um papel crucial nisso e, consequentemente, são abordadas. Portanto, o estudo analisa como esses fatores podem, juntos, formar ’multimonopólios’ de profiling em conexão com uma Internet das Coisas não neutra. Além disso, as técnicas de influência são mais abrangentes onde há falta de consciência e conhecimento, e um novo modelo digital de “dividir para conquistar” parece intensificar esses fenômenos. Ademais, sistemas de pontuação social e preços discriminatórios podem ser ferramentas poderosas nesse sentido. Discutimos a lacuna entre abordagens regulatórias e situações do mundo real, oferecendo ferramentas legais comuns e o Privacy by Design (PbD) como possíveis soluções para acessibilidade neutra. Destacamos como a atual estrutura regulatória exige mais harmonização para garantir proteções efetivas ao usuário, especialmente em um ecossistema de IoT.